GRPC (Golang) master class : build modern API and microservices - Maarek, Stephane (Packt Publishing, 2019)
"GRPC is a new and modern framework for building scalable, modern, and fast APIs. It is leveraged by many top tech companies such as Google, Square, and Netflix and enables programmers to write microservices in any language they want while keeping the ability to easily create communications between these services. It relies on protocol buffers as the transport mechanism and the Service Definition Language. gRPC (Golang) Master Class: Build Modern APIs and Microservices is the best way to get a great overview of all the possibilities offered by gRPC with your favourite language."--Resource description page